Analisis Manajemen Krisis McDonald’s Indonesia dalam Menghadapi Isu Boikot Konsumen - David Krismawan; Bambang Syeh Haryono; Muhammad Syeh Alqadry; R. A. Hadia Alima Syahira; Ahmad In’am Kholifi (Journal of Social, Culture, and Language, 2025)
The global reputational crisis faced by McDonald’s Indonesia due to a wave of boycotts highlights the complexity of organizational communication strategies in responding to public pressure. The main objective of this study is to analyze how the dynamics of organizational communication unfolded through both qualitative and quantitative approaches during the period of July 2023 to March 2024. This research adopts a qualitative descriptive design using narrative data analysis techniques and data collection through online media documentation, as well as quantitative data sourced from the Social Blade platform. The findings indicate that McDonald’s Indonesia experienced a shift in public image from positive to critical due to public reactions to a global issue. The communication strategies implemented during the pre-crisis, crisis, and post-crisis phases were found to be not fully adaptive, as evidenced by a significant decline in Instagram followers and fluctuations in YouTube views. The study also reveals that image recovery occurred slowly, underscoring the importance of aligning communication strategies with the context of the crisis. These findings reinforce crisis communication theory and emphasize the significance of cultural sensitivity and responsiveness in cross-border organizational communication in the digital era.